Use of Systematic Approach in Accident Risk Analysis for Motorcyclists: A Conceptual Idea - da Costa, Don Gaspar Noesaku; Malkhamah, Siti; Suparma, Latif Budi (ITB Journal Publisher, LPPM ITB, 2018)
Thus far, minimum stopping sight distance (SSD) is determined based on design speed, a minimum reaction time of 1.64 s and a deceleration rate of 3.4 m/s², whereas in certain situations the latter can be shorter than 1 s and higher than 4.5 m/s². Awareness of this can trigger speculative behavior, as can be seen from the choice of speed and/or the critical crossing gap, which is often smaller than the recommended minimum SSD. This study focused on the development of an appropriate minimum SSD model that is suited to risky conditions at an un-signalized intersection and its possible usage in accident risk evaluation, particularly for motorcyclists. The data were taken from direct measurements and related studies. Variables that potentially influence minimum SSD were tested. The results strongly suggest that the speed reduction achieved by downshifting significantly influences both the braking distance and the impact speed. Moreover, the minimum SSD obtained from the proposed model significantly differs from that obtained from a similar model recommended by AASHTO. Therefore, it is worthwhile to consider the application of the proposed minimum SSD as an accident probability indicator parameter.